2014
DOI: 10.1097/sla.0000000000000424
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cancer-Associated Genetic Abnormalities in Columnar-Lined Esophagus Tissues With and Without Goblet Cells

Abstract: Objective To determine and compare the frequency of cancer-associated genetic abnormalities in esophageal metaplasia biopsies with and without goblet cells. Background Barrett’s esophagus (BE) is associated with increased risk of esophageal adenocarcinoma (EAC) but the appropriate histologic definition of BE is debated. Intestinal metaplasia (IM) is defined by the presence of goblet cells while non-goblet cell metaplasia (NGM) lacks goblet cells. Both have been implicated in EAC risk but this is controversia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…However, not all studies have corroborated this fi nding ( 12 ). Although DNA content abnormalities appear to be comparable in both metaplastic epithelium without goblet cells compared with metaplastic epithelium with goblet cells, other studies suggest that cancer most commonly occurs in columnar metaplasia with goblet cells compared with columnar metaplasia without goblet cells ( 11,13,14 ). Even if the rate of EAC is markedly higher in CLE containing IM, another complicating factor is sampling error leading to misclassifi cation of IM-containing CLE as non-IM CLE.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…However, not all studies have corroborated this fi nding ( 12 ). Although DNA content abnormalities appear to be comparable in both metaplastic epithelium without goblet cells compared with metaplastic epithelium with goblet cells, other studies suggest that cancer most commonly occurs in columnar metaplasia with goblet cells compared with columnar metaplasia without goblet cells ( 11,13,14 ). Even if the rate of EAC is markedly higher in CLE containing IM, another complicating factor is sampling error leading to misclassifi cation of IM-containing CLE as non-IM CLE.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…In a recent study of 45 BE patients, Bandla et al performed targeted sequencing of all exons from 20 adenocarcinoma-associated genes and found that intestinal metaplasia had a much higher frequency of cancer-associated mutations than non-goblet metaplastic epithelium [69]. In a study of 8522 patients with BE, Bhat S, et al reported that the cancer risk was 0.07% in patients without goblet cells, compared to 0.38% in those with goblet cells at index biopsy (p<0.001) [70].…”
Section: Should Goblet Cells Be Required For the Diagnosis Of Barrettmentioning
confidence: 97%
“…29 However, some studies suggest that metaplastic columnar epithelium without goblet cells may show similar, or even equal, molecular abnormalities to those that occur in patients with goblet cells. 18, 3032 For instances, in a study by Liu et al, 68 patients with BE were analyzed for DNA content by image cytometry and high fidelity histograms.…”
Section: Definition and Diagnostic Criteria Of Barrett’s Esophagusmentioning
confidence: 99%